2019
DOI: 10.1039/c9ay00507b
|View full text |Cite
|
Sign up to set email alerts
|

A rapid room-temperature DNA amplification and detection strategy based on nicking endonuclease and catalyzed hairpin assembly

Abstract: A novel and rapid room-temperature DNA amplification strategy to simultaneously amplify and detect target HIV DNA was developed by coupling catalyzed hairpin assembly (CHA) with a “non-sequence dependent” nicking endonuclease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The calibration curve obtained under the optimized conditions obeyed a double rectangular hyperbola equation with the formula ( R 2 0.9979), where a , b , c , and d were 2.03 × 10 6 , 0.12, 5.86 × 10 7 , and 365, respectively, and may be used to calculate the miRNA-141 concentration in the samples of interest. The curves with similar behaviors were previously reported for assays coupled with CHA/mCHA. ,, The analysis of the calibration curve showed that when the target concentration changed from 1 to 100 pM, the chemiluminescence intensity increased by 8 times, while in many of the miRNA assays reported previously, the signal value changed only by 3–4 times with changing the analyte concentration by 6–7 orders of magnitude. …”
Section: Results and Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The calibration curve obtained under the optimized conditions obeyed a double rectangular hyperbola equation with the formula ( R 2 0.9979), where a , b , c , and d were 2.03 × 10 6 , 0.12, 5.86 × 10 7 , and 365, respectively, and may be used to calculate the miRNA-141 concentration in the samples of interest. The curves with similar behaviors were previously reported for assays coupled with CHA/mCHA. ,, The analysis of the calibration curve showed that when the target concentration changed from 1 to 100 pM, the chemiluminescence intensity increased by 8 times, while in many of the miRNA assays reported previously, the signal value changed only by 3–4 times with changing the analyte concentration by 6–7 orders of magnitude. …”
Section: Results and Discussionsupporting
confidence: 80%
“…The curves with similar behaviors were previously reported for assays coupled with CHA/ mCHA. 28,32,33 The analysis of the calibration curve showed that when the target concentration changed from 1 to 100 pM, the chemiluminescence intensity increased by 8 times, while in many of the miRNA assays reported previously, the signal value changed only by 3−4 times with changing the analyte concentration by 6−7 orders of magnitude. 34−38 Study of Assay Specificity.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…In order to achieve genuine DNA self-replication, nicking endonuclease has been adopted in CHA-based strategies, to produce multiple copies of target DNA with the same sequence. Dong et al 47 coupled CHA with NtÁBsmAI to develop a rapid DNA amplification strategy for the HIV DNA target. The generated CHA product (H1-H2) would hybridize with another hairpin (H3) containing target DNA sequence, thus forming a Y shape DNA structure for the cleavage of NtÁBsmAI and producing massive replicas of target DNA.…”
Section: Nuclease-assisted Methodsmentioning
confidence: 99%
“…With the presence of the target, a pair of harpin probes formed a complex with a replica, which could be cyclically used as a new initiator of harpin probes. The self-replicating CHA has been successfully used to detect DNA and small molecules [ 157 , 158 ].…”
Section: Fully-enzyme-free Cascade Amplificationmentioning
confidence: 99%